Comparative antidiabetic activity of methanolic extract of Operculina turpethum stem and root against healthy and streptozotocin induced diabetic rats - Pulipaka, Shankaraiah; Challa, Srinivasa Reddy; Pingili, Ravindra Babu (International Current Pharmaceutical Journal, 2012)
Diabetes mellitus (DM) consists of a group of syndromes characterized by hyperglycemia. Prevalence of both type 1 and type 2 DM is increasing worldwide, the prevalence of type 2 is rising much more rapidly because of increasing obesity and reduced activity levels as countries become more industrialized. Operculina turpethum, a medicinal plant widely used in the traditional Ayurveda and Siddha systems of medicine for the treatment of diabetes mellitus. The antidiabetic potential of the methanolic extract of O. turpethum stem (MEOTS) and methanolic extract of O. turpethum root (MEOTR) was evaluated in the Streptozotocin (STZ) - induced type 2 diabetic models. The dose 100 mg/kg of MEOTS and MEOTR were administered to normal, glucose loaded and experimental diabetic rats for 21 days. The signi?cantly (p< 0.05) reduction in fasting blood glucose levels were observed in the normal rats at 3 h as well as in the treated diabetic animals at 21 days, thereby justifying the use of the plant in the indigenous system of medicine. DOI: http://dx.doi.org/10.3329/icpj.v1i9.11618 International Current Pharmaceutical Journal 2012, 1(9): 272-278